Science level 1(the city school) (Albakio International,The City school Lahore, 2012)
This curriculum module introduces students to the foundational concepts of science. It covers the scientific method, a systematic approach to inquiry, as well as observation and measurement skills. In the realm of life science, students explore the characteristics of living organisms, the structure and function of plant and animal cells, and basic ecological principles. Physical science concepts such as matter, energy, forces, and motion are also introduced. Finally, the module provides an overview of the Earth's systems, including the atmosphere, hydrosphere, lithosphere, and biosphere.